História e cultura afro-brasileira e indígena: o ensino na UFT de Miracema - Salgado, Poliana Pereira (Universidade Federal do Tocantins, 2021)
The content and form of teaching of Afro-Brazilian and indigenous history and culture are offered by the training discipline at the Federal University of Tocantins, Campus de Miracema, especially in the pedagogy and physical education courses, in the second semester of 2018. Approached by our investigation aiming to comply with Law 11.645 / 2008, which studies schools of basic education, including formative curriculum in AfroBrazilian and indigenous history and culture. This obligation unfolds in vocational training even before teaching in schools. Thus, the study methodology focused on the formative dynamics of the discipline offered on the university campus, specifically the observation, participation and registration of the classes, having as a parameter the discipline plan and thematic seminars with student participation. Analysis of the results of the thematic seminars in Capoeira, Africa and its countries, the laws and the new ethnic-racial legal order, Akwe - Xerente culture and the five main misconceptions of our prejudiced view of the indigenous, and, finally, the seminar on African and Indian board game (mancala and chess), pointed to a significant formation in the ethnic-racial field in fulfillment of the demands of the training in this field. However, they also pointed to a large gap in the specific knowledge of each theme, concluding by the necessary activity of knowledge production in research and extension in the developed field.